Comment on Volodichev et al. Archean Zircons with Omphacite Inclusions from Eclogites of the Belomorian Province, Fennoscandian Shield: The First Finding. Minerals 2021, 11, 1029 - Sergey G. Skublov; Aleksey V. Berezin; Laysan I. Salimgaraeva (Minerals, 2022)
Volodichev et al. (Volodichev et al., 2021) reported on the first finding of omphacite (23%–25% Jd) inclusions in 2.68 Ga metamorphic zircons from Gridino eclogites and presented it as evidence for Archean eclogite-facies metamorphism in the Belomorian Mobile Belt. We believe that the Archean age of the garnets referred to by the above authors was estimated incorrectly. Our interpretation is that omphacite origin is related to Archean high-pressure granulite-facies metamorphism.